Perturbation-based trunk stabilization training in elite rowers - Schäfer, H.; Platen, P. (PLOS ONE, 2021)
Low back pain is a major health issue in elite rowers. High training volume, frequent flexion movements of the lower spine and rotational movement in sweep rowing contribute to increased spinal strain and neuropathological pattern. Perturbation-based trunk stabilization training (PTT) may be effective to treat neuromuscular deficits and back pain. All boat classes (8+, 4+/-, 2-) of the male German national sweep rowing team participated in this non-randomized, parallel group study. We included 26 athletes (PTT: n=12, control group: n=14) in our analysis. Sports therapists conducted 16 individualized PTT sessions á 30-40 minutes in 10 weeks, while the control group kept the usual routines. We collected data before and after intervention on back pain intensity and disability, maximum isometric trunk extension and flexion, jump height and postural sway of single-leg stance. We found less disability (5.3 points, 95% CI [0.4, 10.1], g=0.42) for PTT compared to control. Pain intensity decreased similar in both groups (-14.4 and -15.4 points), yielding an inconclusive between-group effect (95% CI [-16.3, 14.3]). Postural sway, strength and jump height tend to have no between and within-group effects. Perturbation-based trunk stabilization training is possibly effective to improve the physical function of the lower back in elite rowers.